Attitudes towards Integrating Blended Learning into EFL Classrooms:: The Case of Second Year Students at the Department of Letters and the English Language, University of Constantine 1 - Bilouk, Imene (Journal of Human Sciences, 2020)
The present paper is an attempt to reveal undergraduate Algerian learners’ attitudes towards the implementation of blended learning in EFL classrooms. To this end, data were collected using an attitude questionnaire, which contains 36 items divided into three main sections, to a random sample of 60 second year students at the Department of Letters and the English Language-University of Constantine1. The findings indicate that the participants expressed more positive attitudes towards face-to-face learning (M=3.97/SD=.91), whereas, the obtained mean of the positive indicators (M=3.74/SD=.96) was by far higher than the mean of the negative ones (M=2.87/SD=1.06), yielding positive attitudes towards both modalities of teaching/learning in EFL classes, namely face-to-face learning and blended learning, and simultaneously recommending the design of some blended learning courses.